NAIR DA FRANÇA E ARAÚJO: FIRST WOMAN, IN BAHIA, TO OBTAIN A BACHELOR’S DEGREE IN CHEMISTRY - Pinheiro, Bárbara Carine Soares (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Professor Nair from França e Araujo was born in 1931 in the city of Maragogipe, inland Bahia. Daughter of housewife Victorina da França e Araújo, and joiner Elpidio Cyrilo de Araújo, she was the first woman to graduate, in Bahia, with a bachelor’s degree in Chemistry in 1954, when the Course still worked at the Faculty of Philosophy of the University from Bahia, today UFBA. Studied in 1959, the Specialization in Organic Chemistry at the University of São Paulo (USP) and, in 1976, defended his master’s dissertation in Organic Chemistry by developing a research on the synthesis of nitriles starting from aldehydes in organic compounds, in partnership with the Pole Local petrochemical.